Miasis Urogenital: Tinjauan Sistematis Literatur pada Irisan Urologi dan Entomologi - Ishaq, Muhammad Rozaqy; Fitria Dewi Puspita Anggraini (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Urogenital myiasis (UGM) is a rare parasitic disease at the intersection of urology and medical entomology, caused by infestation of the urogenital tract with dipterous fly larvae. Despite its low prevalence, UGM poses significant diagnostic and therapeutic challenges. To systematically review the epidemiology, causative agents, clinical manifestations, diagnosis, and management of urogenital myiasis based on published literature from 2015 to 2025. A comprehensive literature search was conducted using PubMed, Scopus, and Google Scholar databases for articles published between 2015 and 2025. Keywords included "urogenital myiasis," "urinary myiasis," "bladder myiasis," and "genital myiasis." The PRISMA 2020 protocol was used for reporting this systematic review. Of 156 articles identified, 27 articles met the inclusion criteria. UGM accounts for only 0.7% of all human myiasis cases. The most common causative agents are Psychoda species (23.7%) and Cochliomyia species (11.8%). Risk factors include poor hygiene, low socioeconomic status, immunosuppression, and prolonged catheterization. Management involves mechanical removal of larvae, antiseptic irrigation, and adjunctive therapy with ivermectin. UGM remains an underreported condition requiring increased clinical awareness, particularly in developing countries. Early diagnosis and prompt management are essential to prevent complications.